MANAJEMEN BUKU BACAAN BERMUTU UNTUK PENGUATAN LITERASI JENJANG SEKOLAH DASAR - musripin Musripin (Journal of Education Papua Baru, 2025)
Abstract: Literacy development in primary schools requires reading materials that are developmentally appropriate, engaging, and systematically managed. This article examines the management of the Quality Reading Books Program for Level C readers in primary schools. Using a qualitative narrative review design, this study synthesizes journal articles, policy documents, and program guidelines available in the source manuscript, with particular attention to planning, implementation, evaluation, and stakeholder collaboration. The synthesis indicates that quality reading books strengthen literacy when schools implement a cyclical management model encompassing needs diagnosis, collection curation, resource organization, instructional integration, evaluation, and collaborative follow-up. Effective implementation requires reading corners, guided reading, read aloud activities, circulation systems, teacher facilitation, and parental involvement. The novelty of this article lies in its integrated management model emphasizing the transition from fluent reading to meaningful reading for Level C readers, connecting book selection, classroom use, monitoring, family support, and local government policy. Keywords: literacy management; quality reading books; Level C readers; primary school; reading interest.   Abstrak: Penguatan literasi di Sekolah Dasar memerlukan bahan bacaan yang bermutu, sesuai tahap perkembangan pembaca, menarik, dan dikelola secara sistematis. Artikel ini bertujuan menganalisis manajemen Program Buku Bacaan Bermutu pada pembaca Jenjang C di Sekolah Dasar. Dengan desain kajian naratif kualitatif, artikel ini mensintesis artikel jurnal, regulasi, dan dokumen program yang tersedia dalam naskah sumber, terutama terkait perencanaan, pelaksanaan, evaluasi, dan kolaborasi pemangku kepentingan. Hasil sintesis menunjukkan bahwa buku bacaan bermutu berkontribusi terhadap literasi apabila sekolah menerapkan model manajemen siklik yang mencakup diagnosis kebutuhan, kurasi koleksi, pengorganisasian sumber daya, integrasi pembelajaran, evaluasi, dan tindak lanjut kolaboratif. Pelaksanaan program membutuhkan pojok baca, membaca nyaring, membaca bersama, sirkulasi buku, peran guru sebagai fasilitator, dan dukungan orang tua. Kebaruan artikel ini terletak pada model manajemen terpadu yang menekankan transisi dari membaca lancar menuju membaca bermakna bagi pembaca Jenjang C, dengan menghubungkan seleksi buku, pemanfaatan kelas, pemantauan, dukungan keluarga, dan kebijakan pemerintah daerah.  Kata Kunci: manajemen literasi; buku bacaan bermutu; pembaca Jenjang C; sekolah dasar; model manajemen terpadu; transisi membaca.